Validity and reliability of the Turkish version of the Obesity‐Related Well‐Being Questionnaire (ORWELL 97‐TR). Issue 4 (8th January 2022) - Usta, Esra; Bozdemir, Havva; Şen, Sevim
Abstract: Purpose: This study aimed to perform the validity and reliability of the Turkish version of the Obesity‐Related Well‐Being Questionnaire (ORWELL 97‐TR) for the Turkish society. Design and Methods: This methodological study involved 125 people for obesity treatment. Data collection tools were the Patient Information Form, the ORWELL 97‐TR, and the Obesity and Weight‐Loss Quality of Life Instrument (OWLQOL). Findings: The content validity index of the scale was 0.94, and Cronbach's alpha value was 0.906. The findings indicate that the three‐factor structure of the scale, which was reduced from 18 items to 15, showed a good agreement. Practical Implications: The ORWELL 97‐TR scale can be used to assess the life quality of Turkish patients seeking obesity treatment.